The Impact of Arms Proliferation on Social Development in Anambra State Nigeria (2017–2022) - Chinedu, Okoye Emmanuel; Chris, Umeokafor Chibuike; Sunday, Okoye Nonso (ASHA Publishing, 2025)
In recent years, arms proliferation has become a serious threat to peace and development in Nigeria, particularly in areas affected by farmer-herder conflicts. Anambra State, known for its agrarian communities, has experienced growing insecurity that erodes social cohesion and undermines communal welfare. This study adopted a cross-sectional survey design using structured questionnaires to collect data from selected local government areas with a high incidence of conflict. Respondents were purposively sampled from zones identified as high-risk, and data were analyzed using descriptive statistics and the Chi-square test to examine the impact of herdsmen activities on social relationships. Findings revealed widespread disruption of community life due to ongoing clashes, including a decline in hospitality, reduced attendance at cultural festivals, and heightened fear of violence and abductions. The statistical analysis indicated that herders’ activities do not contribute positively to social relationships, as the hypothesis suggesting a positive impact was rejected. The study concludes that arms proliferation has intensified the negative effects of the farmer-herder crisis, threatening sustainable social development across affected communities in Anambra State. In response to these challenges, the research recommends the adoption of community-driven peacebuilding initiatives and the implementation of more rigorous arms control policies. Strengthening local security mechanisms and fostering dialogue between conflicting groups are seen as critical steps toward restoring trust, rebuilding social bonds, and ensuring long-term stability in the region.